Influence of addition surimi wastewater to macronutrient content (nitrogen, phosphor, and potassium) of gracilaria sp. Liquid organic fertilizer - Yudhistira, Ary; Suprapto, Hari; Sulmartiwi, Laksmi (Penerbit Goodwood, 2023)
Purpose: The purpose of this study was to determine the effect of adding surimi wastewater on the increase of nitrogen, phosphorus, and potassium content in Gracilaria sp. liquid organic fertilizer. Research Methodology: This research used an experimental method with a completely randomized design consisting of four treatments (0%, 80%, 90%, and 100% surimi wastewater) and five replications. Macronutrient content (nitrogen, phosphorus, and potassium) in the liquid fertilizer was measured after 14 days of fermentation to evaluate the effect of the treatments. Results: The results showed that the addition of surimi wastewater significantly increased the levels of nitrogen, phosphorus, and potassium in Gracilaria sp. liquid organic fertilizer (P < 0.05). The highest nutrient content was observed in treatments with higher concentrations of surimi wastewater, indicating a positive correlation between wastewater addition and nutrient enrichment. Conclusion: Surimi wastewater can be effectively utilized as an additive in Gracilaria sp. liquid organic fertilizer production to enhance its macronutrient composition. This approach demonstrates potential for sustainable fertilizer development using seafood processing by-products. Limitations: The study was limited by a relatively small sample size and a short observation period, which may restrict the generalizability of the findings. Longer-term studies and larger-scale trials are needed for broader validation. Contribution: This study provides insights into the sustainable utilization of surimi wastewater as a cost-effective nutrient source in liquid organic fertilizers, offering potential benefits for eco-friendly agricultural practices and waste management strategies.